Pengaruh School Climate terhadap School Engagement pada Siswa SMA “X” Kota Bandung - Deanira Laudya; Jane Savitri (Universitas Kristen Maranatha, 2020)
The purpose of this study is to determine the influence of school climate on school engagement on students of “X” senior high school in Bandung. 297 students participated in this study. The research method used is causal relationship. Quesionnaire of school engagement based on Fredricks, Blumenfeld, and Paris’s theory (2004). Quesionnaire of school climate based on Thapa, Cohen, Higgins-D’Alessandro, and Guffey’s theory (2013). The research data obtained then analyzed with a simple linear regression test with SPSS version 20. The result is school climate influence in increasing school engagement (? = 0.625, R2 = 0.390 and p = 0,000). School climate also influence the three types of school engagement, namely behavioral engagement (? = 0.503, R2 = 0.253 and p = 0,000)), emotional engagement (? = 0.596, R2 = 0.356 and p = 0,000), and cognitive engagement (? = 0.425, R2 = 0.204 and p = 0,000). Based on the results of this study, the researcher suggestfor further researchers to investigate the role of teachers support, peer support, individual need and other variables that also can influence school engagement. The Researcher also suggest to principal and teacher to be able to create more positive school climate. Keywords: school climate, school engagement, student